Epidemiological characteristics, distribution of axial length, and prevalence of ocular abnormalities associated with congenital cataract in Northwest China: a 16-year cross-sectional study (2008–2023) - He, Mengmei; Gong, Min; Dou, Guorui; Zhou, Jian; Hou, Xu (Frontiers in Medicine, 2025)
BackgroundWe aimed to identify epidemiological characteristics, distribution of axial length and ocular abnormalities associated with congenital cataract in Northwest China.MethodsThis observational cross-sectional study evaluated patients with congenital cataracts who underwent surgery between 2008 and 2023. Patient characteristics were compared among different age groups and hospitalization years.ResultsA total of 527 patients (527 eyes) underwent cataract surgeries. Of these, 323 patients (61.29%) resided in rural areas and 204 (38.71%) in urban regions. Rural patients exhibited a higher median age at surgery (36[6,72] months) compared to urban counterparts (23.5[4,64] months), with a significant difference between them (Z = −2.543, p = 0.011). Median surgical age differs significantly across hospitalization year subgroups (χ2 = 40.636, p < 0.001). Axial length demonstrated accelerated growth prior to 2 years of age, with statistically significant interocular differences in unilateral cases below 24 months (p < 0.05). Congenital cataract cases were predominantly diagnosed between 2 and 6 years (32.26%). Age distribution patterns significantly varied across hospitalization periods (χ2 = 70.394, p < 0.001). Ocular abnormalities alone were present in 293 cases (55.60%), while 40 patients (7.59%) exhibited concurrent systemic abnormalities. Amblyopia emerged as the most frequent ocular comorbidity (23.34%).ConclusionRural patients constituted a higher proportion of congenital cataract. The median surgical age demonstrated a significant difference across hospitalization year subgroups. Axial growth patterns showed significant correlations with surgical timing, sex, and laterality. These findings indicate enhanced parental awareness of pediatric ocular health and provide an evidence-based rationale for early intervention strategies in congenital cataracts in Northwest China.